Proteomic signature for detection of high‐grade ovarian cancer in germline BRCA mutation carriers. Issue 4 (23rd October 2022) - Bahar‐Shany, Keren; Barnabas, Georgina D.; Deutsch, Lisa; Deutsch, Netanel; Glick‐Saar, Efrat; Dominissini, Dan; Sapoznik, Stav; Helpman, Limor; Perri, Tamar; Blecher, Anna; Katz, Guy; Yagel, Itai; et al.
Abstract: No current screening methods for high‐grade ovarian cancer (HGOC) guarantee effective early detection for high‐risk women such as germline BRCA mutation carriers. Therefore, the standard‐of‐care remains risk‐reducing salpingo‐oophorectomy (RRSO) around age 40. Proximal liquid biopsy is a promising source of biomarkers, but sensitivity has not yet qualified for clinical implementation. We aimed to develop a proteomic assay based on proximal liquid biopsy, as a decision support tool for monitoring high‐risk population. Ninety Israeli BRCA1 or BRCA2 mutation carriers were included in the training set (17 HGOC patients and 73 asymptomatic women), (BEDOCA trial; ClinicalTrials.gov Identifier: NCT03150121). The proteome of the microvesicle fraction of the samples was profiled by mass spectrometry and a classifier was developed using logistic regression. An independent cohort of 98 BRCA mutation carriers was used for validation. Safety information was collected for all women who opted for uterine lavage in a clinic setting. We present a 7‐protein diagnostic signature, with AUC >0.97 and a negative predictive value (NPV) of 100% for detecting HGOC. The AUC of the biomarker in the independent validation set was >0.94 and the NPV >99%. The sampling procedure was clinically acceptable, with favorable pain scores and safety. We conclude that the acquisition of Müllerian tract proximal liquid biopsies in women at high‐risk for HGOC and the application of the BRCA ‐specific diagnostic assay demonstrates high sensitivity, specificity, technical feasibility and safety. Similar classifier for an average‐risk population is warranted. Abstract : What's new? There is no diagnostic test for early stage high‐grade ovarian cancer (HGOC), so women at high risk are recommended to have their ovaries and fallopian tubes surgically removed. However, the surgery comes with some unwanted side effects. Here, the authors present a 7‐protein signature for detecting HGOC in a proximal liquid biopsy from the uterine cavity. The protein assay distinguished between patients and controls with high sensitivity, and the sampling method was clinically acceptable with respect to pain and safety. This approach could help assist women carrying BRCA mutations and their physicians determine the appropriate timing for prophylactic surgery.